Selective Attention and Concentration Are Related to Lifestyle in Chilean Schoolchildren - Felipe Caamaño-Navarrete; Pedro Ángel Latorre-Román; Juan Párraga-Montilla; Daniel Jerez-Mayorga; Pedro Delgado-Floody (MDPI AG, 2021)
The objective of this investigation was to determine the association between selective attention and concentration with physical fitness (i.e., cardiorespiratory fitness (CRF), <semantics><mover accent="true">V˙</mover></semantics>O2max, the standing long jump test (SLJ) and handgrip muscle strength (HGS)), lifestyle parameters (i.e., physical activity (PA) level, screen time (ST), sleep duration and food habits) and anthropometric measures (i.e., body mass index (BMI) and waist circumference (WC)) among Chilean schoolchildren. Two hundred and forty-eight schoolchildren (137 boys, 111 girls, 11.80 ± 1.17 and 11.58 ± 1.09 years, respectively) participated. Selective attention, concentration and lifestyle (PA, ST, sleep duration and Mediterranean diet (MD) adherence) were determined using a standard questionnaire. CRF, SLJ, HGS and anthropometric indicators (BMI and WC) were also measured. Selective attention showed a positive association with MD adherence score (β; 5.012, p = p < 0.05). Concentration was linked inversely to ST (β; −5.498, p = p < 0.05). Likewise, concentration presented a positive association with MD adherence (β; 2.904, p = p < 0.05). In conclusion, children's lifestyles are related to the selective attention and concentration of children; therefore, promoting healthy habits could be a cost-effective strategy in the promotion of cognitive development, as it relates to selective attention and concentration.